Unassimilable Strangeness: The Afrikaans Poetry of Olga Kirsch - Roth, Egonne (Department of Dutch and South African Studies, Faculty of English, 2013)
The Afrikaans poetry of Olga Kirsch (1924-1997) makes an important and lasting contribution to Afrikaans literature, despite its “unassimilable strangeness.” In a genre dominated until then by men, Kirsch introduces the voice of a woman poet; more importantly, she is the only Jewish poet in Afrikaans. And Kirsch seals her ‘strangeness’ by her early, initial critique of apartheid policies. Kirsch also wrote in English and Hebrew, but her published output in Afrikaans is more significant and will ultimately determine her place in the national canon and the cultural consciousness of post-apartheid South Africa.
Keywords: Olga Kirsch; Afrikaans; Jewish poet; woman poet; gender studies; Afrikaans literature; war poetry